Optimization of Recommender Systems Using Particle Swarms - Nancy Yaneth Gelvez Garcia; Jesús Gil-Ruíz; Jhon Fredy Bayona-Navarro (Ingeniería, 2023)
Background: Recommender systems are one of the most widely used technologies by electronic businesses and internet applications as part of their strategies to improve customer experiences and boost sales. Recommender systems aim to suggest content based on its characteristics and on user preferences. The best recommender systems are able to deliver recommendations in the shortest possible time and with the least possible number of errors, which is challenging when working with large volumes of data.